Degree of Implementing TQM at Graduate Program: Misrata University - Mohamed O. Al-Ghazal; Mohamed R. Shoayb (University of Science and Technology, Yemen, 2014)
Degree of Implementing TQM at Graduate Program: Misrata University Abstract:  The recent world challenges in forces education institutions to follow a awareness scientific method to face these challenges and to utilize effective capability of human that characteristics by flexibility and high efficiency. The most important aspect in education that considered as a reference is total quality standards. Because of high order information and communication techniques the total quality standards were become a distinguished aspect of modern human thinking. That was clear specially in educational institutions, general institutions and committee. To develop education in Libya according to 17 Feb. revolution that aims to reduce ignorance and shortage in education, it should apply quality in educational institutions including higher studies. The recent research aims to identify the degree of applying quality standards of higher studies at education department. The importance of the research comes from drawing determination of strategies and drawing plans that promote the effectiveness of education development at Faculties and universities. Also, this research has benefit in developing teaching methods and higher studies programs. The results of the research showed that all standards in the List achieved more than 65%; however they rages from (69.34-89.56%)     Keywords: standards, quality standards, higher studies.